2009
DOI: 10.1007/s10725-009-9417-5
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of benzyladenine with meta-topolin during shoot multiplication increases acclimatization of difficult- and easy-to-acclimatize sea oats (Uniola paniculata L.) genotypes

Abstract: Benzyladenine (BA) is the only cytokinin to effectively induce shoot multiplication in vitro between genotypes of the important dune grass species Uniola paniculata (sea oats). However, a significant genotypespecific negative carryover effect of BA on ex vitro acclimatization has been observed. In the present study, the effects of multiplication media supplemented with metatopolin (mT), a BA-analog, BA or no plant growth regulator, were compared on in vitro multiplication, rooting and ex vitro acclimatization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 14 publications
4
22
0
Order By: Relevance
“…Williams) compared to BA (Bairu et al 2008). Valero-Aracama et al (2010) observed that mT at 10 lM or higher had inhibitory effects on the in vitro rooting of two Uniola paniculata genotypes. Similarly, Escalona et al (2003) in a study on plantain cv.…”
Section: Effect On Rooting and Ex Vitro Acclimatizationmentioning
confidence: 94%
See 1 more Smart Citation
“…Williams) compared to BA (Bairu et al 2008). Valero-Aracama et al (2010) observed that mT at 10 lM or higher had inhibitory effects on the in vitro rooting of two Uniola paniculata genotypes. Similarly, Escalona et al (2003) in a study on plantain cv.…”
Section: Effect On Rooting and Ex Vitro Acclimatizationmentioning
confidence: 94%
“…Consequently, these metabolites interfere with rooting and acclimatization competence in micropropagated plantlets (Werbrouck et al 1995). As demonstrated by Valero-Aracama et al (2010), BA treatment caused detrimental biochemical, physiological and developmental effects in Uniola paniculata cultures that resulted into reduced acclimatization competence. The authors discovered that similar problems were absent in mT treatments; which is a further indication of the relative lower toxicity of mT over BA and its analogues.…”
Section: Effect On Rooting and Ex Vitro Acclimatizationmentioning
confidence: 99%
“…One possible improvement of the procedures is in the choice of cytokinin. In micropropagation usually benzylaminopurine (BAP) is added but another cytokinin, metatopolin, is often just as effective with respect to the breaking of apical dominance (so resulting in a similar propagation factor) but has less negative side-effects (Bogaert et al 2006;Valero-Aracama et al 2009; but see Bairu et al 2008).…”
Section: Is Epigenetic Variation Caused By Stress?mentioning
confidence: 99%
“…BA is the first-generation artificial synthetic cytokinin, and known as one of effective PGRs widely used for in vitro propagation of sea oats (Valero-Aracama et al 2010), shoot regeneration of Tripterospermum japonicum (Moon et al 2009) and Anthocephalus cadamba (Kavitha et al 2009), shoot tip culture for horseradish propagation , and so on. TDZ, which has been highly effective in many in vitro plant propagation trials, is one of non-purine synthetic cytokinins, and known as a PGRs used among wide range of species (Amutha et al 2006), such as Vitex trifolia L. (Ahmed and Anis 2012), Salix tetrasperma R. , and butterfly pea (Seemab et al 2012).…”
Section: Discussion Shoot Inductionmentioning
confidence: 99%